Measurement of charge-dependent directed flow in STAR Beam Energy Scan (BES-II) Au+Au and U+U collisions - Taseer Muhammad Farhan (EPJ Web of Conferences)
We presented the rapidity dependence of directed flow (v1) and its slope (dv1/dy) for π±, K± and P(P¯) in Au+Au collisions at √sNN = 7.7 − 19.6 GeV from the Beam Energy Scan Phase-II, as well as in U+U collisions at √sNN = 193 GeV measured by the STAR experiment. The v1 values are reported as a function of rapidity and centrality. Additionally, the dv1/dy and the charge dependent difference, △(dv1/dy), of the three identified particles in U+U collisions is compared to those in Au+Au and isobar (Ru+Ru and Zr+Zr) collisions. These findings offer insights into the initial electromagnetic field as well as baryon transport at various system sizes and beam energies.